Efektivitas Penggunaan Google Classroom Terhadap Hasil Belajar Bahasa Jepang Siswa SMAN 16 Jakarta - Citra Nurani Jelita; Hendri Zalman (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2022)
This research is motivated by the average Japanese language value of 10th grade students below the KKM, which is 75, because they are unable to study effectively in a pandemic situation. This study aims to describe the effectiveness of learning using google classroom on students' Japanese learning outcomes. Population of this study were all 10th grade students of SMAN 16 Jakarta as many as 280 people. Meanwhile, for the sampling, the researcher used purposive sampling technique and the sample was class 10 Mipa 1 SMAN 16 Jakarta which consisted of 40 students as the experimental class. The method used in this research is quantitative with the type of quasi-experimental research and pretest-posttest design. The test instrument is in the form of multiple choices objective test. The results revealed that the t test of the sig value test. > significant 0.05 (0.722 > 0.05). This indicates that H0 is acceptable. Based on the results of the t-test, it can be concluded that learning using google classroom on students' Japanese learning outcomes is not effective.